2019
DOI: 10.1002/ehf2.12397
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of human mesenchymal cells isolated from the right ventricle and epicardial fat differ strikingly both directly after isolation and long‐term culture

Abstract: Aims Mesenchymal stromal cells isolated from different tissues are claimed to demonstrate similar therapeutic potential and are often incorrectly named mesenchymal stem cells. However, through comparison of such cells is lacking. This study aimed to compare the transcriptome of mesenchymal cells of the same phenotype isolated from the heart muscle and epicardial fat of the same patient, before and after culture. Methods and results Cells were isolated from biopsies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…It seems that the donor of the tissue, tissue collection method, and what is more isolation and expansion protocols influence secretion and transcription profile of isolated MSC, causing a difficult issue to compare the results between different laboratories. Additionally, Stępniewski et al recently revealed that cells expressing the same mesenchymal markers and isolated from human heart tissue (right ventricle and epicardial fat) have distinct transcriptomes [10]. Taken together our observations concerning donor-specific secretion profile, further treatments based on mesenchymal cells need to be reevaluated.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It seems that the donor of the tissue, tissue collection method, and what is more isolation and expansion protocols influence secretion and transcription profile of isolated MSC, causing a difficult issue to compare the results between different laboratories. Additionally, Stępniewski et al recently revealed that cells expressing the same mesenchymal markers and isolated from human heart tissue (right ventricle and epicardial fat) have distinct transcriptomes [10]. Taken together our observations concerning donor-specific secretion profile, further treatments based on mesenchymal cells need to be reevaluated.…”
Section: Discussionmentioning
confidence: 72%
“…The major issue is the heterogeneity of MSC population [7]. Despite meeting all the criteria of the International Society for Cellular Therapy (ISCT) [8], namely (1) plastic adherence in standard culture conditions, (2) defined expression of specific markers (CD73, CD90, CD105) along with lack of expression of hematopoietic markers (CD14, CD34, CD45, HLA-DR) and (3) differentiation potential into adipocytes, osteoblasts, and chondroblasts in vitro, MSC may differ in secretome and/or transcriptome profile depending on the donor of the tissue or the site of collection [5, 9, 10]. An additional drawback is the isolation and expansion protocols varying between laboratories.…”
Section: Introductionmentioning
confidence: 99%